The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1071/ea08122
|View full text |Cite
|
Sign up to set email alerts
|

An on-farm evaluation of the capability of saline land for livestock production in southern Australia

Abstract: Grazing livestock on revegetated saline land is one of few profitable options to continue using this class of agricultural land. However, there has been little research conducted to assess the capability of saline land to support livestock production based on the soil and water characteristics at a particular site. In this study, data from 11 grazing studies collected from eight commercial farms across southern Australia were used to estimate metabolisable energy (ME) utilised/ha, as well as total ME produced/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Despite these limitations, saltbush is a valuable source of CP, sulfur, vitamin E and some essential minerals (Ben Salem et al 2010;Pearce et al 2010;Fancote et al 2013;Norman et al 2019). A collaborative research project, involving farmers, agronomists, livestock scientists and system modellers, identified low FV, particularly ME content, as the key constraint that limited profitability of saltbush systems (Thomas et al 2009). Pre-experimental modelling indicated that improving shrub organic-matter digestibility by 10% would increase profits by three times the increment associated with increasing biomass production by 10%, or reducing the cost of establishment by 10% (O'Connell et al 2006).…”
Section: Case Study 4: Variability In Nutritional Value Of a 'Wild' S...mentioning
confidence: 99%
“…Despite these limitations, saltbush is a valuable source of CP, sulfur, vitamin E and some essential minerals (Ben Salem et al 2010;Pearce et al 2010;Fancote et al 2013;Norman et al 2019). A collaborative research project, involving farmers, agronomists, livestock scientists and system modellers, identified low FV, particularly ME content, as the key constraint that limited profitability of saltbush systems (Thomas et al 2009). Pre-experimental modelling indicated that improving shrub organic-matter digestibility by 10% would increase profits by three times the increment associated with increasing biomass production by 10%, or reducing the cost of establishment by 10% (O'Connell et al 2006).…”
Section: Case Study 4: Variability In Nutritional Value Of a 'Wild' S...mentioning
confidence: 99%
“…The daily ME intake (MEI) of the ewes was calculated using the method of Thomas et al (2009), where liveweight gain or loss, in combination with the animal's current liveweight, are used to predict the MEI of the animal.…”
Section: Metabolisable Energy Intakementioning
confidence: 99%
“…A multiple linear-regression analysis was conducted to examine the relationships between estimated MEI (dependent variable) and the number of sheep grazing days on stubble, and initial sheep liveweight and body condition score (independent variables). Both sheep grazing days (ewe days/ha, not adjusted for liveweight) and dry sheep equivalent (DSE) grazing days (DSE days/ha, 1 DSE = 8.9 MJ ME/day; Thomas et al 2009) variates were used in analyses. For linear-regression analyses for variates predicting MEI, sheep grazing days (unadjusted for ME requirements) was included as a fixed effect because initial sheep liveweight was included in the statistical model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Saltbush plantations on mixed farms may also foster biodiversity in the landscape (Seddon et al 2009;Collard and Fisher 2010) via the provision of habitat for animals. Recent research (Norman et al 2008(Norman et al , 2010Thomas et al 2009;Llewellyn et al 2013), and the recognition of increased productivity of otherwise marginal land, has highlighted the important role of perennial shrubs in the low to medium rainfall zones of Australia (Revell et al 2013).…”
Section: Introductionmentioning
confidence: 99%